2016
DOI: 10.5474/geologija.2016.001
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemistry and isotope geochemistry of Velenje Basin groundwater

Abstract: The geochemical and isotopic composition of groundwater in the Velenje Basin, Slovenia, was investigated between the years 2014 to 2015 to identify the geochemical processes in the major aquifers (Pliocene and Triassic) and the water-rock interactions. Thirty-eight samples of groundwater were taken from the aquifers, 19 in the mine and 19 from the surface. Groundwater in the Triassic aquifer is dominated by HCO , and Si, and has high alkalinity, with δ 13C DIC values in the range of -14.4 to +4.6 ‰. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…To date, Giammanco et al [50] investigated the interactions between gas-water-rock in shallow aquifers in the Šaleška valley and used multivariate PCA to determine different geochemical processes affecting groundwater quality. Later, Kanduč et al [40] performed a geochemical, isotopic characterization of surface waters and deep groundwater in aquifers dewatering Pliocene and Triassic strata. They found that in the Triassic aquifer HCO 3 − , Ca 2+ and Mg 2+ ions prevail and groundwater δ 18 O and δ 2 H values are close to those of surface waters when plotted on the meteoric global meteoric line and that the 3 H data indicate recent recharge.…”
Section: Characteristics Of the Velenje Basin And Groundwater From Prmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, Giammanco et al [50] investigated the interactions between gas-water-rock in shallow aquifers in the Šaleška valley and used multivariate PCA to determine different geochemical processes affecting groundwater quality. Later, Kanduč et al [40] performed a geochemical, isotopic characterization of surface waters and deep groundwater in aquifers dewatering Pliocene and Triassic strata. They found that in the Triassic aquifer HCO 3 − , Ca 2+ and Mg 2+ ions prevail and groundwater δ 18 O and δ 2 H values are close to those of surface waters when plotted on the meteoric global meteoric line and that the 3 H data indicate recent recharge.…”
Section: Characteristics Of the Velenje Basin And Groundwater From Prmentioning
confidence: 99%
“…Temperature, pH, dissolved oxygen (DO) and electrical conductivity were measured with Multiset 3430 (WTW) in the field and are reported in [40]. For trace elements, all sampling bottles were pre-cleaned with 10% HCl and washed with ultra-pure distilled water.…”
Section: Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratio of 0.71942 ± 0.00026 is a result of silicate weathering. Moreover, groundwaters from a coal mine in Velenje were investigated; outflowing from the Pliocene clastic aquifer have Sr ratio of 0.70820–0.71056, while from the Triassic carbonates 0.70808–0.70910 (Kanduč et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%